Sistem Informasi Manajemen Proyek Berbasis Web di PT Mitra Tekno Nusantara - Dewa, Tatas Sasmita; Hastomo, Mursid Dwi; Pantjarani, Ari (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
The project management information system is the  most crucial process in controlling all development activities od an application in a technology-based company. Project management is very important as a from of accountability and tool to make it easier for companies to control every application development activity by programmers. PT Mitra Tekno Nusantara is an agency engaged in the development of software application such a websites, desktop, android and IoT. This agency has problem reporting the application development process and checking members on duty, which are still carried out using Whats Up, telephone or face-to-face meetings, which causes problems when reviewing source code, checking client data and seeing members in charge responsible for application development. This of course has a negative impact on the developments of the company. The purpose of this research is to create a project management information system at PT Mitra Tekno Nusantara Sukoharjo. The author uses the SDLC (System Development Life Cycle) method in the system development process and the PHP programming language and uses the MySQL database. The system that the author design is expected to produce application that can view client data, software developer members on duty and download application development reports that are currently running at PT Mitra Tekno Nusantara and can be access via the web so that leaders can access it flexibly anywhere and anytime.Keywords: PHP, MYSQL, SDLC, Information System